Analisis Kebutuhan Hierarki Abraham Maslow Terhadap Tokoh Rebecca Pada Novel Dear Nathan-Hello Salma Karya Erisca Febriani - Aisyah Nur Shahara; Ranfa Kinanti; Eva Dwi Kurniwan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to analyze the self-actualization of Rebecca's character in the novel entitled